Special Significance of Non-Drosophila Insects in Aging - Guo, Siyuan; Wang, Xianhui; Kang, Le (Frontiers in Cell and Developmental Biology, 2020)
Aging is the leading risk factor of human chronic diseases. Understanding of aging process and mechanisms facilitates drug development and the prevention of aging-related diseases. Although many aging studies focus on fruit fly as a canonical insect system, minimal attention is paid to the potentially significant roles of other insects in aging research. As the most diverse group of animals, insects provide many aging types and important complementary systems for aging studies. Insect polyphenism represents a striking example of the natural variation in longevity and aging rate. The extreme intraspecific variations in the lifespan of social insects offer an opportunity to study how aging is differentially regulated by social factors. Insect flight, as an extremely high-intensity physical activity, is suitable for the investigation of the complex relationship between metabolic rate, oxidative stress, and aging. Moreover, as a “non-aging” state, insect diapause not only slows aging process during diapause phase but also affects adult longevity during/after diapause. In the past two decades, considerable progress has been made in understanding the molecular basis of aging regulation in insects. Herein, the recent research progress in non-Drosophila insect aging was reviewed, and its potential utilization in aging in the future was discussed.